Association of COVID‐19 with impaired endothelial glycocalyx, vascular function and myocardial deformation 4 months after infection. (13th September 2021) - Lambadiari, Vaia; Mitrakou, Asimina; Kountouri, Aikaterini; Thymis, John; Katogiannis, Konstantinos; Korakas, Emmanouil; Varlamos, Charalampos; Andreadou, Ioanna; Tsoumani, Maria; Triantafyllidi, Helen; Bamias, Aristotelis; Thomas, Konstantinos; et al.
Abstract: Aims: SARS‐CoV‐2 infection may lead to endothelial and vascular dysfunction. We investigated alterations of arterial stiffness, endothelial coronary and myocardial function markers 4 months after COVID‐19 infection. Methods and results: In a case‐control prospective study, we included 70 patients 4 months after COVID‐19 infection, 70 age‐ and sex‐matched untreated hypertensive patients (positive control) and 70 healthy individuals. We measured (i) perfused boundary region (PBR) of the sublingual arterial microvessels (increased PBR indicates reduced endothelial glycocalyx thickness), (ii) flow‐mediated dilatation (FMD), (iii) coronary flow reserve (CFR) by Doppler echocardiography, (iv) pulse wave velocity (PWV), (v) global left and right ventricular longitudinal strain (GLS), and (vi) malondialdehyde (MDA), an oxidative stress marker, thrombomodulin and von Willebrand factor as endothelial biomarkers. COVID‐19 patients had similar CFR and FMD as hypertensives (2.48 ± 0.41 vs. 2.58 ± 0.88, P  = 0.562, and 5.86 ± 2.82% vs. 5.80 ± 2.07%, P  = 0.872, respectively) but lower values than controls (3.42 ± 0.65, P  = 0.0135, and 9.06 ± 2.11%, P  = 0.002, respectively). Compared to controls, both COVID‐19 and hypertensives had greater PBR5–25 (2.07 ± 0.15 µm and 2.07 ± 0.26 µm, P  = 0.8 vs. 1.89 ± 0.17 µm, P  = 0.001), higher PWV (carotid–femoral PWV 12.09 ± 2.50 vs. 11.92 ± 2.94, P  = 0.7 vs. 10.04 ± 1.80 m/s, P  = 0.036) and impaired left and right ventricular GLS (−19.50 ± 2.56% vs. −19.23 ± 2.67%, P  = 0.864 vs. −21.98 ± 1.51%, P  = 0.020 and −16.99 ± 3.17% vs. −18.63 ± 3.20%, P  = 0.002 vs. −20.51 ± 2.28%, P  < 0.001). MDA and thrombomodulin were higher in COVID‐19 patients than both hypertensives and controls (10.67 ± 0.32 vs 1.76 ± 0.03, P  = 0.003 vs. 1.01 ± 0.05 nmol/L, P  = 0.001 and 3716.63 ± 188.36 vs. 3114.46 ± 179.18 pg/mL, P  = 0.017 vs. 2590.02 ± 156.51 pg/mL, P  < 0.001). Residual cardiovascular symptoms at 4 months were associated with oxidative stress and endothelial dysfunction markers. Conclusions: SARS‐CoV‐2 may cause endothelial and vascular dysfunction linked to impaired cardiac performance 4 months after infection.